Study Of Automatic Devices Of Spinning Yarn Weighting Machine (Texas Journal of Engineering and Technology, 2024)
At present, the following main technological factors are controlled and automatically adjusted in carding machines: thread tension in zones, elongation, pressure of compression shafts, temperature in the drying part of the carding frame, carding level in the hopper, moisture content of carded yarn, weaving weight the density of the package at the bottom. Threads spun in a spinning machine are mainly dipped in liquid spinning, the excess of the required amount is squeezed out, and then dried. In the front part of the machine, the yarns coming from different spools are separated from each other and wound on the weaving spool.